Analisis Daya Saing dan Faktor-faktor yang Memengaruhi Ekspor Karet Indonesia ke India - Pramudita, Galuh; Harisudin, Mohamad; Widadie, Fanny (Politeknik Negeri Lampung, 2025)
Indonesia, as the second largest rubber producer in the world, has exported rubber to various countries; India is one of the leading destinations for rubber export. However, many factors can affect Indonesian rubber exports to India. This study aims to analyze the competitiveness of Indonesian rubber exports in India and the international market and to determine the factors that can affect Indonesian rubber exports to India. The data used are secondary data from 2005 to 2022 obtained by FAO, ITC, BPS, World Bank, and Bank Indonesia. Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), and Export Competitiveness Index (ECI) methods to analyze the competitiveness of rubber export. Multiple linear regression analysis to analyze the factors that affect exports. The study results show that the competitiveness of Indonesian rubber exports in the Indian market is strong, although it fluctuates. The competitiveness of Indonesian rubber exports in the international market is dominated by strong export competitiveness, but it has had weak competitiveness. Production factors and land area have a significant and positive effect, exchange rates and export prices have a negative impact, and producer prices and India’s GDP per capita do not significantly affect exports. This states that increasing the export competitiveness and volume of Indonesian rubber exports to India can be done by increasing rubber production to increase the supply of export rubber.